2016
DOI: 10.1038/srep21703
|View full text |Cite
|
Sign up to set email alerts
|

The cannabinoid quinol VCE-004.8 alleviates bleomycin-induced scleroderma and exerts potent antifibrotic effects through peroxisome proliferator-activated receptor-γ and CB2 pathways

Abstract: Scleroderma is a group of rare diseases associated with early and transient inflammation and vascular injury, followed by fibrosis affecting the skin and multiple internal organs. Fibroblast activation is the hallmark of scleroderma, and disrupting the intracellular TGFβ signaling may provide a novel approach to controlling fibrosis. Because of its potential role in modulating inflammatory and fibrotic responses, both PPARγ and CB2 receptors represent attractive targets for the development of cannabinoid-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(98 citation statements)
references
References 39 publications
1
87
0
Order By: Relevance
“…Additionally, the regulation of the endocannabinoid was demonstrated not only as a possible etiology, but also as a possible treatment. Experimental fibrosis mice treated with either VCE‐004.8 (CB2 and peroxisome proliferator‐activated receptor γ agonist), WIN55,212‐2 (CB1 and CB2 agonist), or JWH‐115 (CB2 agonist) display a reduction in disease severity . The in vivo experiment results are also supported by in vitro evidence.…”
Section: Cannabis and Autoimmune Diseasesmentioning
confidence: 62%
“…Additionally, the regulation of the endocannabinoid was demonstrated not only as a possible etiology, but also as a possible treatment. Experimental fibrosis mice treated with either VCE‐004.8 (CB2 and peroxisome proliferator‐activated receptor γ agonist), WIN55,212‐2 (CB1 and CB2 agonist), or JWH‐115 (CB2 agonist) display a reduction in disease severity . The in vivo experiment results are also supported by in vitro evidence.…”
Section: Cannabis and Autoimmune Diseasesmentioning
confidence: 62%
“…More recent studies showed that an antagonist of the CB2R augments collagen synthesis in association with TGF‐β1 signaling and SMAD phosphorylation (Li et al, ). In addition, agonists of PPARγ and CB2Rs (julemic acid or the compound VCE‐004.8, respectively), promote anti‐fibrotic responses in experimental models of systemic sclerosis (Del Río et al, ; González et al, ). Moreover, activation of CB2Rs provokes anti‐fibrotic responses through the inhibition of the TGF‐β1/SMAD pathway in a Nrf2 dependent manner (Li et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, CB 2 receptor activation limits leukocyte infiltration and tissue fibrosis (Akhmetshina et al, 2009). Thereby, structurally different CB 2 agonists such as ajulemic acid, JHW-133 and VCE-004.8 have been shown to alleviate skin fibrosis and inflammation in experimental SSc (Akhmetshina et al, 2009;Gonzalez et al, 2012;del Rio et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…PPARγ was initially identified through its role in the regulation of glucose and lipid metabolism and cell differentiation, but it is now well established that PPARγ agonists are also exhibit anti-inflammatory and anti-fibrotic effects (Clark, 2002;Dantas et al, 2015). In this regard, PPARγ is a regulator of connective tissue homeostasis, and different experimental approaches have shown that PPARγ ligands attenuate hepatic (Galli et al, 2002), renal (Bae et al, 2017) and pulmonary fibrosis (Milam et al, 2008) as well as bleomycin-induced skin fibrosis (Gonzalez et al, 2012;Wei et al, 2014;del Rio et al, 2016;Ruzehaji et al, 2016).…”
Section: Introductionmentioning
confidence: 99%